2022
DOI: 10.4103/1673-5374.336134
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of interleukin-27 as a regulator of neuronal survival in central nervous system diseases

Abstract: Interleukin-27 is a pleiotropic cytokine that is involved in tissue responses to infection, cell stress, neuronal disease, and tumors. Recent studies in various tissues indicate that interleukin-27 has complex activating and inhibitory properties in innate and acquired immunity. The availability of recombinant interleukin-27 protein and mice with genetic deletions of interleukin-27, its receptors and signaling mediators have helped define the role of interleukin-27 in neurodegenerative diseases. Interleukin-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recently, two newly discovered cytokines namely, IL‐27 and IL‐33 have drawn great attention of researchers in the pathogenesis of MS. IL‐27, a novel heterodimeric cytokine belonging to the IL‐12 superfamily, is predominantly produced by the APCs which can exert either positive or negative regulatory effects upon immune responses (Xu et al, 2017). IL‐27 is of critical importance in the limitation of autoimmune diseases and CNS inflammation in several experimental models and it's the anti‐inflammatory effects of IL‐35 are not only manifested in the suppression of Th1 and T17 responses but also are characterized by the promotion of Treg cells (Mascanfroni et al, 2013; Nortey et al, 2022). Importantly, it has also been reported that mice that lack the receptor for IL‐27 or IL‐27‐downstream signaling transcription factors are highly linked to susceptibility to EAE (Fitzgerald, Ciric, et al, 2007; Peters et al, 2015), and continuous infusion and delivery of IL‐27 has been shown to ameliorate neuropathology in EAE (Casella et al, 2017; Fitzgerald, Zhang, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two newly discovered cytokines namely, IL‐27 and IL‐33 have drawn great attention of researchers in the pathogenesis of MS. IL‐27, a novel heterodimeric cytokine belonging to the IL‐12 superfamily, is predominantly produced by the APCs which can exert either positive or negative regulatory effects upon immune responses (Xu et al, 2017). IL‐27 is of critical importance in the limitation of autoimmune diseases and CNS inflammation in several experimental models and it's the anti‐inflammatory effects of IL‐35 are not only manifested in the suppression of Th1 and T17 responses but also are characterized by the promotion of Treg cells (Mascanfroni et al, 2013; Nortey et al, 2022). Importantly, it has also been reported that mice that lack the receptor for IL‐27 or IL‐27‐downstream signaling transcription factors are highly linked to susceptibility to EAE (Fitzgerald, Ciric, et al, 2007; Peters et al, 2015), and continuous infusion and delivery of IL‐27 has been shown to ameliorate neuropathology in EAE (Casella et al, 2017; Fitzgerald, Zhang, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, "interleukin-27-mediated signalling pathway" was enriched for > 100 folds. The role of interleukin-27 (IL-27) in regulating T cell responses that prevent immune hyperactivity has been extensively characterized and IL-27 has been investigated as a possible therapeutic for chronic inflammatory conditions with excessive T cell activation, which includes MS [22].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, “interleukin-27-mediated signalling pathway” was enriched for > 100 folds. The role of interleukin-27 (IL-27) in regulating T cell responses that prevent immune hyperactivity has been extensively characterized and IL-27 has been investigated as a possible therapeutic for chronic inflammatory conditions with excessive T cell activation, which includes MS [22]. On the other hand, the anti-inflammatory capability of IL-27 can also be induced from other cell types in the central nervous system such as macrophages, microglia, and dendritic cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibits neuroinflammation and promotes neuroprotection and repair by inhibiting the production of pro-inflammatory cytokines and promoting the differentiation of type 1 regulatory T cells [15] IL-35…”
Section: Il-2mentioning
confidence: 99%